2011
DOI: 10.1016/j.scispo.2010.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of three different water temperatures on dehydration in competitive swimmers

Abstract: Aims\ud The purpose of this study was to evaluate the effects of three different water temperatures on physiological responses (dehydration, sweat rate, urine output, rectal temperature and plasma electrolytes) of competitive athletes during a “simulated” race of 5 km in an indoor swimming pool.\ud Methods\ud Nine male competitive master swimmers swam 5 km with the water at temperatures of 23, 27 and 32 ̊C. Immediately before (Pre) and after (Post) each trial, samples of blood and urine were collected, body we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 19 publications
0
29
0
1
Order By: Relevance
“…Macaluso and colleagues (2011) reported increasing levels of hypohydration and core temperature when swimmers completed a 5-km time trial in three different water temperatures (23, 27, and 28 °C). Although moderate levels (2%) of dehydration were reported when swimmers completed the time trial in 32 °C water, rises in core temperature were mild (36.9 ± 0.4 to 38.0 ± 0.4 °C; Macaluso et al, 2011). Similar levels of weight loss have been seen in swimmers completing 2 hr of flume swimming at similar water temperatures (personal observations, David Gerrard, Otago University).…”
Section: Kmmentioning
confidence: 71%
“…Macaluso and colleagues (2011) reported increasing levels of hypohydration and core temperature when swimmers completed a 5-km time trial in three different water temperatures (23, 27, and 28 °C). Although moderate levels (2%) of dehydration were reported when swimmers completed the time trial in 32 °C water, rises in core temperature were mild (36.9 ± 0.4 to 38.0 ± 0.4 °C; Macaluso et al, 2011). Similar levels of weight loss have been seen in swimmers completing 2 hr of flume swimming at similar water temperatures (personal observations, David Gerrard, Otago University).…”
Section: Kmmentioning
confidence: 71%
“…In humans, a water temperature slightly lower than body temperature was found to decrease heart rate [20] , while water temperature higher than body temperature resulted in an increased heart rate [16] . This can be explained by the fact that swimming in water with a temperature lower than body temperature can cause peripheral vasoconstriction, resulting in increased blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers have studied the effects of water temperature in animal models and in humans [1,[9][10][11][12][13][14][15][16] . Those reports found that low water temperature close to body temperature resulted in longer exercise compared to higher water temperature close to body temperature and very low temperature (lower than 20°C), respectively.…”
Section: Makale Kodu (Article Code): Kvfd-2013-9710mentioning
confidence: 99%
“…In addition, ambient environmental temperatures may play a significant role on T C regulation during aqueous exercise (Macaluso et al, 2011;Soler et al, 2003). Therefore, the higher sweat rates may also be partially attributable to the participants still becoming accustomed to the altered climatic conditions (Hue et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Reportedly, sweat rates in male swimmers range between 0.33 and 2.7L·hr -1 (Cox, Broad, Riley, & Burke, 2002;Hue et al, 2004;Lemon, Deutsch, & Payne, 1989;Maughan et al, 2009;Macaluso et al, 2011;Soler, Echegaray, & Rivera, 2003) and 0.30 L·hr -1 for female swimmers (Cox et al, 2002;Maughan et al, 2009). In addition, previous research has shown sweat rates increase as water temperature (McMurray & Horvath, 1979;Macaluso et al, 2011) or exercise intensity increases (Cox et al, 2002). For example, in elite male water polo players, the demands of competition resulted in sweat rates and fluid intake more than twice that of the training environment (Cox et al, 2002).…”
mentioning
confidence: 99%